2017
DOI: 10.1177/2309499017713937
|View full text |Cite
|
Sign up to set email alerts
|

Endoprosthetic replacement versus cement spacer in reconstruction of proximal humerus after tumor resection: Cost and benefits

Abstract: Background: Proximal end of the humerus is a common site for both primary and metastatic bone tumors. Limb salvage with endoprosthetic replacement is the most common means of reconstruction, but it has been proved that cement spacer are more beneficial for inferior shoulder function. Thus, limb salvage can be replaced by cheaper spacers especially in poor societies. Patients and methods: This study included 20 patients, of whom 14 were female, with a mean age of 40.4 years (range 12-60). Among the study popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Although the function results were satisfactory, the score of lifting ability was still the lowest one in all the scoring. The previous reports 17, [21][22][23][24][25][26][27][28][29][30] showed the functional scores after proximal humerus prosthesis reconstruction ranged from 60 to 80%.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although the function results were satisfactory, the score of lifting ability was still the lowest one in all the scoring. The previous reports 17, [21][22][23][24][25][26][27][28][29][30] showed the functional scores after proximal humerus prosthesis reconstruction ranged from 60 to 80%.…”
Section: Discussionmentioning
confidence: 90%
“…The previous reports (systematic review with 341 patients) 30 showed large discrepancy of prosthesis survival in different studies which ranged from 38 to 100%. The incidence of complications was between 5 and 22% in different reports 17,[21][22][23][24][25][26][27][28][29][30] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Patients with metastatic bone disease are not only concerned about whether the disease is curable, but also about the impact of treatment on their QOL. As a result, oncologists treat these patients with the aim of improving their QOL 1,13. In many clinical trials, a QOL assessment scale was used to evaluate the effectiveness of treatment, especially when it comes to incurable disease 14.…”
Section: Discussionmentioning
confidence: 99%
“…The proximal humerus is a common site of bone metastasis. Lesions at this location often occur in the advanced stages of cancer 1. Pathological fractures of the proximal humerus are common, and usually require a long time to heal, while up to 50% of the cases never heal 3.…”
Section: Introductionmentioning
confidence: 99%